Use of Dental Services and Oral Health-Related Quality of Life in Preschool Children: Dental services and quality of life in preeschool children - Keila Lais Carrera da Hora; Tatiana Frederico Almeida; Maria Cristina Teixeira Cangussu (CV Media Inti Teknologi, 2026)
Background: Oral health issues, particularly cavities, significantly impact children's eating, sleeping, speech, and overall well-being. The COVID-19 pandemic has worsened these problems by increasing disparities in access to dental care.Aims: To analyse the use of dental services and their impact on oral health-related quality of life (OHRQoL) in preschool children in Salvador, identifying associated factors.Methods: A cross-sectional study was conducted among 523 children aged 26 to 80 months enrolled in municipal public daycare centres in Salvador, BA. Oral health assessments and a caregiver questionnaire were used to collect sociodemographic data, dietary and oral health habits, and dental service use. OHRQoL was assessed using the B-ECOHIS. Descriptive and multivariate analyses were performed using linear regression at the 95% significance level.Results: The prevalence of caries was 41.87%, and the use of dental services during the pandemic was low (13.58%). Age, family income, dental caries, and fear/anxiety were significantly associated with the B-ECOHIS, highlighting inequalities in access to services and in children's oral health-related quality of life (OHRQoL). There was no association between dental service use and OHRQoL.Conclusion: The COVID-19 pandemic reduced preschoolers’ use of dental services, worsening OHRQoL and highlighting social inequalities and the need for equitable preventive oral health care.